THE MAPPING THE POTENTIAL OF THE OLD CITY TOURISM (Study of the History, Region and Cultural Value of the Old City on Bangka Island) - Cholilah, Jamilah; Herdiyanti, Herdiyanti; Wijayanti, Nurvita; Hidayat, Novendra (Faculty of Social and Political Sciences University of Bangka Belitung, 2019)
This research is entitled Mapping the Tourism Potential of the Old City (Study of the History, Region and Cultural Value of the Old City on Bangka Island). The research objective was to map the tourism potential of the old city in Bangka Island, namely Belinyu and Muntok Districts. Overview this social mapping is divided into three aspects which include history, territory and cultural values. The problems in this study are formulated in three main questions, namely (1) How is the distribution of the old cities of Muntok and Belinyu based on Chinese, Malay and European clusters? (2) How does the distribution of the Chinese, Malay and European clusters affect the tourism promotion of the old city in Muntok and Belinyu? (3) How does Toponimi affect the tourism promotion of old cities in Muntok and Belinyu?The location of the study was conducted in Belinyu and Muntok Districts. The consideration is based on the search results of secondary data showing that these two regions were formerly known as the central areas of the Dutch colonial government (Muntok) and the center of tin mining activities (Belinyu).The research method used is descriptive qualitative research with social mapping techniques. Sources of data in this study include primary and secondary data. Primary data is obtained by means of interviews and direct observation from the speakers. Secondary data was obtained from reference books, research journals, and references through the internet that were related to the tourism potential of the old city.